Stem Cell Therapy for Modulating Neuroinflammation in Neuropathic Pain - Joshi, Hari Prasad (Int J Mol Sci, 2021)
Neuropathic pain (NP) is a complex, debilitating, chronic pain state, heterogeneous in nature and caused by a lesion or disease affecting the somatosensory system. Its pathogenesis involves a wide range of molecular pathways. NP treatment is extremely challenging, due to its complex underlying disease mechanisms. Current pharmacological and nonpharmacological approaches can provide long-lasting pain relief to a limited percentage of patients and lack safe and effective treatment options. Therefore, scientists are focusing on the introduction of novel treatment approaches, such as stem cell therapy. A growing number of reports have highlighted the potential of stem cells for treating NP. In this review, we briefly introduce NP, current pharmacological and nonpharmacological treatments, and preclinical studies of stem cells to treat NP. In addition, we summarize stem cell mechanisms—including neuromodulation in treating NP. Literature searches were conducted using PubMed to provide an overview of the neuroprotective effects of stem cells with particular emphasis on recent translational research regarding stem cell-based treatment of NP, highlighting its potential as a novel therapeutic approach.